Study the Performance of Different Packing in Open Cooling Towers - Nsaif Abbas, Mohammed (Journal of Engineering and Sustainable Development, 2012)
The effect of different shapes (corrugate, and grid) of packing on the performance in air -water-cooling tower were addressed in this research. A mechanical forced draught counter current flow-cooling tower of (40 * 40) cm cross-sectional area and 1.5 m high was constructed. Airflow rates of 0.4,1.4, and 2 kg/m2.s were used in conjunction with water flow rates of 1.5, 2, and 2.5 kg/m2.s, and water temperature of 40, 45, 50 0C. The tower characteristics (KG a Z/L) over all volumetric mass transfer coefficient(KGa) volumetric heat transfer coefficient in gas phase (hGa) and volumetric heat transfer coefficient in liquid phase (hla) are found to be a function of the water and airflow rates simultaneously. The numerical analysis was done by preparing computer program to reduce each set of data obtain form the plant and to evaluate the performance coefficient, volumetric owns transfer coefficient, volumetric heat transfer coefficient.The work was extended to include the longitudinal and transverse temperature profiles within the tower for different parameters. By employing packed heights of 100, 75, 50 and 25 cm, end effects were studied, and the tower characteristics (KG a Z/L) corrected from these effects. Least square method was used to correlate the experimental results for (KG a Z/L) in terms of air flux G and water flux L.